A New Search Direction for Full-Newton Step Interior-Point Method in P*(κ)-HLCP. (27th July 2019) - Kheirfam, B.
Abstract: In this article, a full-Newton step feasible interior-point algorithm for P * ( κ ) -horizontal linear complementarity problems is proposed that uses a new method for identifying search directions. The method is based on a simple equivalent form of the centering equations of the system which defines the central path. The theoretical complexity of the new algorithm is derived which coincides with the best-known iteration bound for P * ( κ ) -horizontal linear complementarity problems.